Ultrasmall Au-GRHa Nanosystem for FL/CT Dual-Mode Imaging-Guided Targeting Photothermal Therapy of Ovarian Cancer - Liu, Annan; Li, Lei; Wang, Ze; Li, Xingchen; Liang, Hao; Yang, Jingpu; Nešić, Maja D.; Yang, Xiaoyu; Lin, Quan (Analytical chemistry (Washington), 2025)
As the most common and lethal cancer of the female gonads, ovarian cancer (OC) has a grave impact on people’s health. OC is asymptomatic, insidious in onset, difficult to diagnose and treat, fast-growing, and easy to metastasize and has poor prognosis and high mortality. How to detect OC as early as possible and treat it without side effects has become a challenging medical problem. Herein, the ultrasmall Au-GRHa nanosystem was designed for dual-mode imaging-guided photothermal therapy of OC. The synthesized Au-GRHa nanosystem has ultrasmall size, good biocompatibility, and excellent fluorescence and CT imaging performance, which could detect the OC tumor accurately and intuitively and is expected to provide intraoperative visual navigation for clinical surgery. With its excellent photothermal property, the Au-GRHa nanosystem can be utilized for photothermal therapy of OC, thus providing an alternative to, and reducing the hazards posed by, traditional radiotherapy and chemotherapy. In addition, GnRHa endows the AuNDs with excellent ability to target the Gonadotropin-Releasing Hormone Receptor (GnRH-R), which enhances the uptake of AuNDs by OC tumor cells, improving the targeting accuracy and efficacy of photothermal therapy for OC. This work will facilitate the biomedical applications of the Au-GRHa nanosystem and provide good insights into FL/CT imaging-guided photothermal therapy of OC.